2014
DOI: 10.1007/s10689-014-9732-5
|View full text |Cite
|
Sign up to set email alerts
|

Cribriform-morular variant of papillary thyroid carcinoma: an indication to screen for occult FAP

Abstract: Cribriform-morular variant (CMV) is a rare subtype of papillary thyroid carcinoma (PTC) that is associated with familial adenomatous polyposis (FAP). Given the high likelihood for multi-organ malignancies in FAP patients, this study explores the yield of diagnosing occult FAP among CMV-PTC patients. Institutional database was searched in order to identify patients with pathologically-confirmed CMV-PTC from 2000 to 2012. Medical records were reviewed, and clinical and pathological features were analyzed. Eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
1
18
1
2
Order By: Relevance
“…However, the authors did not present the prevalence of CMV-PTC. The third large series of CMV-PTC was reported by Levy and coworkers in Memorial Sloan Kettering Cancer Centre in the USA in 2014 (Levy et al 2014). The authors identified 11 patients with CMV-PTC of 6901 patients with papillary thyroid carcinoma in the period from 2001 to 2012.…”
Section: Epidemiologymentioning
confidence: 97%
“…However, the authors did not present the prevalence of CMV-PTC. The third large series of CMV-PTC was reported by Levy and coworkers in Memorial Sloan Kettering Cancer Centre in the USA in 2014 (Levy et al 2014). The authors identified 11 patients with CMV-PTC of 6901 patients with papillary thyroid carcinoma in the period from 2001 to 2012.…”
Section: Epidemiologymentioning
confidence: 97%
“…Alternatively, histologically similar morular structures have been reported in the cribriform-morular variant of papillary thyroid carcinoma (CMVPTC) [32]. Although sporadic examples of CMVPTC have been reported, this rare histopathologic subtype is strongly associated with FAP syndrome [33,34]. Specifically, 1-2 % of the patients with FAP develop papillary thyroid carcinoma and 20-40 % of these tumors are diagnosed as CMVPTC [35,36].…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, 1-2 % of the patients with FAP develop papillary thyroid carcinoma and 20-40 % of these tumors are diagnosed as CMVPTC [35,36]. The presence of a cribriform-morular architectural pattern in thyroid cancer has been considered an indicator for occult FAP necessitating appropriate patient evaluation [34,37]. It appears possible that germline or acquired mutations in genes of the Wnt/b-catenin pathway, such as APC, may correlate with a morular phenotype in a variety of benign or malignant neoplasms arising in the thyroid gland or odontogenic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that FAP patients are usually diagnosed with TC at a younger age than the general population [27], in which the median age of diagnosis is 50 years (range 45–54) [4]. Similarly, in PR, the median age of diagnosis for TC in the general population in males and females is 54 and 50 years, respectively [5].…”
Section: Discussionmentioning
confidence: 99%